THE INFLUENCE OF INTELLECTUAL CAPITAL ON FIRM VALUE, WITH FINANCIAL PERFORMANCE AS A MODERATING VARIABLE - Ari Widi Prakasa (SEAN Institute, 2022)
The market's favorable impression of a firm rests in large part on the value of the company's intangible assets, including its intellectual capital. This research aims to examine the connection between intellectual capital and corporate value via the lens of financial performance. This study uses data from 2016-2019 to analyze a sample of companies that are members of the Jakarta Islamic Index (JII). Worth Added Intellectual Coefficient (VAIC) is a measure of intangible assets, Return on Assets (ROA) is a measure of financial performance, and Price to Book Value is a measure of firm value (PBV). Based on the data presented here, it appears that (1) intellectual capital significantly improves financial performance, (2) intellectual capital has no effect on business value, and (3) financial performance can mediate the relationship between intellectual capital and firm value.